Japan’s senior employment challenge - Takao, Yasuo (Crawford School of Public Policy at the Australian National University, 2025)
Faced with an aging population and acute labour shortages, Japan has boosted senior employment through policy. Yet many seniors are working out of financial necessity, not choice. As demographic decline makes longer working lives more common, Japan must ensure that they are voluntary and dignified. Fair wage structures and inclusive employment systems are essential to making extended employment sustainable and equitable.